2020
DOI: 10.1016/j.ccm.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health Effects of Exposure to Cleaning Products

Abstract: Cleaning-related respiratory health effects are an important occupational and public health issue • A wide variety of respiratory symptoms and conditions have been reported• Many cleaning agents have hazardous properties which may lead to health effects via several underlying mechanisms• Preventive measures to avoid the cleaning-related respiratory health burden are warranted SYNOPSISThere is consistent and growing evidence of an epidemic of 'asthma-like' symptoms among professional cleaners. Important questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Epidemiological research on health effects from cleaning and disinfection agents generally focus on cleaning and nursing occupations ( Quirce and Barranco, 2010 ; Van den Borre and Deboosere, 2018 ; Carder et al , 2019 ; De Matteis et al , 2020 ; Dumas and Le Moual, 2020 ; Archangelidi et al , 2021 ; Romero Starke et al , 2021 ). To some extent the SWEA data confirm expected patterns regarding in which sectors and occupations diseases and injuries occur, however, the full range of sectors and occupations covered by the ISA data show the wide-spread use of this product group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological research on health effects from cleaning and disinfection agents generally focus on cleaning and nursing occupations ( Quirce and Barranco, 2010 ; Van den Borre and Deboosere, 2018 ; Carder et al , 2019 ; De Matteis et al , 2020 ; Dumas and Le Moual, 2020 ; Archangelidi et al , 2021 ; Romero Starke et al , 2021 ). To some extent the SWEA data confirm expected patterns regarding in which sectors and occupations diseases and injuries occur, however, the full range of sectors and occupations covered by the ISA data show the wide-spread use of this product group.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies point towards links between use of cleaning agents and lung disease ( Quirce and Barranco, 2010 ; Van den Borre and Deboosere, 2018 ; Carder et al , 2019 ; De Matteis et al , 2020 ; Dumas and Le Moual, 2020 ; Archangelidi et al , 2021 ; Romero Starke et al , 2021 ). A Belgian registry study found increased mortality in respiratory and cardiovascular diseases among cleaners ( Van den Borre and Deboosere, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If replicated, our findings may help improving the recognition and management of irritant-induced work-related asthma. Other studies, in an epidemiological or clinical setting, and possibly including additional relevant pathways for irritant-induced asthma, such as neurogenic inflammation involving transient receptor potential (TRP) channels [39] would be useful to further characterize asthma endotypes related to irritant exposures.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent and growing evidence of an epidemic of asthma‐like symptoms among professional cleaners 1 . Cleaning tasks are associated with exposure to several chemical agents with potential harmful effects to the respiratory system 2 .…”
Section: Introductionmentioning
confidence: 99%